The effect of the Er: YAG laser on the clinical success of hydrophilic fissure sealant: a randomized clinical trial - Hülya Yılmaz; Sultan Keleş (European Oral Research)
Purpose The aim of this study was to assess the effect of the Er:YAG laser on the clinical success of a hydrophilic fissure sealant over 12 months.Subject and Methods This study was conducted on 132 permanent first molars from 44 (19 girls and 25 boys) patients aged 7-11 years. The teeth were divided into three groups. The first group (Group A-control) of teeth were etched with phosphoric acid, the second group of teeth (Group L) were etched with an Er:YAG laser, and the third group of teeth (Group A+L) were etched with both the Er:YAG laser and phosphoric acid. Clinical evaluations were performed at baseline and at 3-, 6-, 9- and 12-month follow-up visits. The data were analyzed with Pearson chi-square tests, Cochran Q tests and Kaplan-Meier analysis.Results At the end of the 12 months, total retention rates were 72.7%, 59.1%, and 65.9% in the acid group, the laser group and the laser and acid group, respectively. Although there was no statistically significant difference between group retention rates (p>0.05), the lowest retention rate was found in the laser group at the end of the 12-month follow-up period. No new caries were observed in any group during the study period.Conclusion Etching with the Er:YAG laser, phosphoric acid or a combination of both methods provided similar results for the clinical success of hydrophilic based fissure sealant.